Food processing: The use of non-fouling food grade heat transfer fluids. (5th June 2015) - Wright, Christopher Ian; Bembridge, Thomas; Picot, Eole; Premel, Julien
Abstract: It is reported that there are some 4000 companies operating high temperature thermal fluid systems in the UK and Ireland. This excludes steam or water based systems. The heat transfer fluids (HTFs) used in food processing are highly refined mineral HTFs that are non-toxic, non-irritating and lack an odour. If an HTF has been certified for use in food processing it carries an HT-1 certificate. HTFs suitable for use in food processing are commonly referred to as 'non-fouling' which means as they thermally degrade they produce small carbon particles that are suspended in the HTF. Moreover, the carbon formations are less sticky and this reduces the extent of adhesion to the internal surfaces of an HTF system. The current paper analysed the test reports from 1223 HTF systems and showed that, on average, the carbon residue for food grade HTF was lower than non-food grade HTF. This clearly demonstrates what the non-fouling nature of a food grade HTF. This paper then explored the regulatory, legal and environmental landscape for food grade HTFs. In this area of manufacturing, it is critical that the HTFs used are suitable for incidental contact with food. Other measures put consumer safety at the heart of all operations (i.e., internal company procedures such as hazard analysis and critical control points [HACCP]) and that food is safe for consumer consumption (e.g., external controls such as auditing manufacturers to ensure good quality and distribution practice). The authors introduce the idea that safety could be further enhanced through independent HTF sampling and chemical analysis of HTFs to ensure they are food grade and should be done without any interruption to a manufacturer's production. Highlights: Food grade heat transfer fluid (HTF) is colourless, non-toxic and non-irritating. This HTF is non-fouling and less carbon forms. Such HTFs can be safely used in food processing if they are HT-1 certified. A number of controls (e.g., HACCP) are used to ensure such fluids are safe. An additional check is to sample fluids to ensure food grade fluids are being used.